2020
DOI: 10.1029/2020jd032495
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vertically and Obliquely Propagating Gravity Waves in Influencing the Polar Summer Mesosphere

Abstract: Using an 8-year (2007-2014) data set from two different limb-viewing instruments, we evaluate the relative roles of vertically versus obliquely propagating gravity waves (GWs) as sources of GWs in the polar summer mesosphere. Obliquely propagating waves are of interest because they are presumed to be generated by the summer monsoons. In the high-latitude upper mesosphere, the correlation coefficient between the time series of ice water content (IWC) and GW amplitude is 0.48, indicating that the observed GWs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 70 publications
4
29
0
Order By: Relevance
“…These summer hemisphere MLT maximums of GWs over high‐latitude region is consistent with the results from the gravity wave regional or global ray tracer (GROGRAT) model (Preusse et al, 2009). One possible source of these waves is obliquely propagating GWs that originate from the lower latitude (e.g., Thurairajah et al, 2020).…”
Section: Observational Resultsmentioning
confidence: 99%
“…These summer hemisphere MLT maximums of GWs over high‐latitude region is consistent with the results from the gravity wave regional or global ray tracer (GROGRAT) model (Preusse et al, 2009). One possible source of these waves is obliquely propagating GWs that originate from the lower latitude (e.g., Thurairajah et al, 2020).…”
Section: Observational Resultsmentioning
confidence: 99%
“…From model simulations, Sato et al (2009) showed that the latitudinal shear in the prevailing westward jet, that has a slanted structure from the tropical stratosphere to the polar mesosphere, could refract these monsoon generated GWs to the high-latitude mesosphere. The oblique propagation (or latitudinal but vertical propagation away from the source) has been reported in model studies (e.g., Kalisch et al, 2014) and observations (e.g., Thurairajah et al, 2017Thurairajah et al, , 2020Yasui et al, 2016). Yasui et al (2016) used mesospheric wind data from Antarctica and precipitation data from the tropics and found that a significant component of the mesospheric GWs in the high-latitude summer SH originates from tropical convection (i.e., monsoon regions).…”
mentioning
confidence: 82%
“…We use the version 2.0 level 2A SABER temperature data. Previous studies have shown that in the vertical wavelength range of 4-20 km, SABER is sensitive to horizontal wavelengths greater than 500 km (Thurairajah et al, 2020 and references therein). However, SABER can observe GWs with horizontal wavelengths as short as 100 km depending on the distance between two subsequent altitude profiles (e.g., Ern et al, 2018).…”
Section: Monsoon Convection and Gravity Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using the KANTO model, Sato et al (2009Sato et al ( , 2012 showed evidence of lateral propagation of GWs and provided theoretical explanations of the mechanisms involved. Conducting ray-tracing simulations, Yamashita et al (2013) also suggested that high GW activity in the MLT during ES events observed by the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) on the Thermosphere, Ionosphere, Mesosphere Energetics Dynamics (TIMED) satellite is caused by poleward propagating GWs (Thurairajah et al, 2020). To understand the middle atmosphere dynamics in which behavior of the GWs is one of the key processes, state-of-the-art GW-permitting GCMs provide an effective approach.…”
Section: Of 22mentioning
confidence: 99%